Molecular epidemiology of otomycosis in Isfahan revealed a large diversity in causative agents. Issue 6 (June 2019) - Aboutalebian, Shima; Mahmoudi, Shahram; Mirhendi, Hossein; Okhovat, Ahmadreza; Abtahi, Hamidreza; Chabavizadeh, Javaher
Abstract : Purpose. : To elucidate the clinical and microbial epidemiology of otomycosis in Isfahan, Iran. Methodology. : From January 2016 to January 2017 all patients clinically suspected of otomycosis at Al‐Zahra Hospital, Isfahan, Iran were recruited. Specimens were taken using sterile swabs by an otorhinolaryngologist and subjected to culture and microscopy using potassium hydroxide and Giemsa stain. Isolated fungi were identified based on morphological and molecular characteristics. Results. : Otomycosis was confirmed in 97/120 patients (80.8 %). Females (72.2 %) and patients aged 30‐39 years (33 %) were more commonly affected than others. Manipulation of ear canal (62.9 %) was the most common predisposing factor. Pruritus was observed in 84.54 % of the patients followed by hearing impairment (81.4 %), and most episodes were detected over the summer (50.5 %). Culture was positive for 81 (83.5 %) of confirmed cases and molds were the most prevalent causative agents ( n =51, 63 %) followed by yeasts ( n =19, 23.4 %) and yeast/mold mixes ( n =11, 13.6 %). For the 16 remaining patients, no growth was seen in culture despite a positive result on direct examination. In total, 92 isolates (63 molds and 29 yeasts) were recovered in culture. Application of molecular methods showed 18 fungal species and the vast majority of them belonged to Aspergillus ( n =53, 57.6 %) and Candida genus. Among the species involved, Candida parapsilosis ( n =22, 22.7 %) and Aspergillus tubingensis ( n =15, 15.5 %) were the most encountered species. Conclusion. : Outcomes from this study showed a different picture of prevalence, where C. parapsilosis and A. tubingensis but not Aspergillus niger were the most species encountered from patients suffering from otomycosis.